Pengaruh Model WE-ARe terhadap Metacognitive Skills Mahasiswa - Adiansyah, Romi; Muliana, Muliana; Muh. Amin, Astuti; Asfat, M. Lutfi; Sanusi, Suharyono Afrian (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
Students' metacognitive skills can be developed through implementing learning designs that are consistent with students' learning needs and progress. The WE-ARe (Warm-up, Exploring, Argumentation, Resume) model is a learning model that can be used to accommodate students' increased metacognitive skills. The aim of this research is to analyze the influence of the WE-ARe model on the metacognitive skills of biology students at Universitas Muhammadiyah Bone. This research uses a quasi-experimental research design, pretest-posttest control group design. The research sample was students from the Biology Education Study Program Semester III (three) at Universitas Muhammadiyah Bone, totaling 41 people in two classes. The research instrument uses essay questions and questionnaires. The data were analyzed descriptively and inferentially. The research results show that the Fcount value is 2470.273 with a significance value of 0.000. The significance value is smaller than the alpha real level of 5% (0.05), so it can be concluded that there is a difference in metacognitive skills between the experimental group and the conventional group. The research conclusion is that there is an influence of the WE-ARe model on the metacognitive skills of biology students at Universitas Muhammadiyah Bone.